IMPLEMENTATION OF CHECK-IN SERVICE BY THE RECEPTIONIST AT HOTEL THE ZURI PEKANBARU - Br Sitorus, Lamria Meliani Nopita; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Receptionists have an important role in the hotel world, especially in receiving and welcoming guests, therefore the authors are interested in conducting research on the implementation of check-in services at The Zuri Pekanbaru Hotel, because the hotel is a 4-star hotel in Pekanbaru, the authors also want to know the Implementation of Services Check-in by the receptionist at the hotel is in accordance with the SOP (Standard Operational Procedure) check-in. based on this research the authors collect data through interviews, observation and documentation. And the results of this study the authors found that the implementation of check-in services at The Zuri Pekanbaru Hotel was quite good but still imperfect because there were still employees who did not carry out their duties based on existing SOPs, this was due to a lack of manpower, resulting in less receptionist meticulous at work due to being overwhelmed in handling busy check-in guests, there is also the attitude of the receptionist who is not friendly towards guests and also because of the inflexible working hours of employees. Keywords: Service Implementation, Receptionist, Check-in, Hotel The Zuri Pekanbaru